Export Stimuli, Export Stages and Internationalization Pathways: The Case of Indonesian SMEs - Revindo, Mohamad D. (UI Scholars Hub, 2016)
Small and Medium-sized Enterprises (SMEs) in developing countries are still constrained to seize the opportunity of trade liberalization as compared to their large counterparts. It has been argued that effective efforts to foster SME export require clear understanding of the factors that stimulate them to export. This study investigates the export stimuli of 385 Indonesian SMEs at different export stages (pre-exporting and exporting) and different internationalization pathways (domestically established exporter and born-global SMEs). Three types of export stimuli are consistently identified as the most important in all sub-samples: the presence of foreign buyers, the confidence in the products and the aspiration to find alternative markets. By contrast, two types of export stimuli are consistently found as the least important in all sub-samples: government support and Indonesian diaspora communities. The academic and policy implications of the findings are discussed.